Proposta de adequação do sistema bombeamento-reservação de um setor da Cidade Universitária Professor José da Silveira Netto - Belém (PA) - SOUZA, Marianna de Oliveira (2021)
Study objective: updating of a computional model of water reservation in operation, in search of improvements in the operational adjustments of the system, aiming at reducing costs with pumping electric power and better utilization of the reservoir, so that demand is met. Methodology/approach: three stages of simulations were performed in two different scenarios using the software EPANET 2.0, where the models were compared to verify the best use of high reservoir (HR) and higher energy efficiency. Originality/relevance: having a water supply system in a satisfactory condition is an important element for the wellness of a community. In this way, we seek projects and solutions that allow access to water in an economical way, since one of the biggest costs in a supply system is concentrated in the pumping system. In addition, at peak times the price charged per (kWh) has a higher cost. Main results: the simulations showed that the current HR was not meeting the demand, and even with improvements in the operation there were still negative pressures in some moments. Therefore, it was suggested the implementation of an additional reservoir, which met the demand and managed to reduce electricity costs by 36.13%. Contributions: operational improvements in water pumping and reservoir systems. Conclusions: in addition to improvements in the operation of the reservoir, the construction of a new one is also necessary, since the campus is always expanding, and the investment will bring a future return with the reduction of expenses with electricity.